Experimental infection by Borrelia anserina strain PL in Gallus gallus - Marcio Barizon Cepeda; Matheus Dias Cordeiro; Bruna de Azevedo Baêta; Adivaldo Henrique da Fonseca (Semina: Ciências Agrárias, 2021)
Avian borreliosis is a tick-borne acute septicemic disease that affects a variety of avian species and is caused by the bacterium Borrelia anserina. The present study aimed to establish the infection dynamics of B. anserina in experimentally infected Gallus gallus to determine its impact on the health and weight gain of the animals. Forty G. gallus were divided into four groups. Group 1 (G1) included 10 animals inoculated intramuscularly (IM) with 250?L of blood serum containing 3.7x106 spirochetes per milliliter. Group 2 (G2) included 10 animals inoculated IM with 250?L of saline 0.9%. Group 3 (G3) included 10 animals infested with four Argas miniatus nymphs (3rd instar) infected with B. anserina strain PL. Group 4 (G4) included 10 animals infested with four A. miniatus nymphs (3rd instar) free of infection by B. anserina. The number of spirochetes in the blood was directly proportional to the appearance of clinical signs and symptoms. This is the first study showing the experimental clinical evolution of the B. anserina PL strain in G. gallus. Additionally, the first assessments of spirochetaemia are presented, based on the direct count of bacteria in the serum by a Neubauer chamber, during the infection.